KARDİYOPULMONER ’’BY-PASS’IN’’ TRAKEAL TÜP BALON BASINCINA ETKİSİ - EROLÇAY, Hülya; YÜCEYAR, Lale; AYKAÇ, Bora (Cerrahpaşa Medical Journal, 2014)
Background.- The effects of hypotension and hypothermia on tracheal tube cuff pressure during cardiac surgery were assessed in this study. Design.- Twelve patients were included and a standardized general anesthesia was applied to the patients entubated with the proper size Portex Profile endotracheal tubes. Cuffs were inflated with air to a pressure of 20 cmH2O. Pilot balloons of the tubes were connected to a device which measures the intracuff pressure as H2O. Nonpulsatile perfusion was used during cardiopulmoner by-pass (CPB) and mean arterial pressure (MAP) was kept within 40-70mmHg. Body temperature was cooled to 280C (rectal). MAP, esophageal temperature and cuff pressure were recorded every 5 minutes during the operation. Data were collected at eight intervals: 1: after surgical incision, 2: after sternotomy, 3: just before the CPB, 4:5 minutes after aortic cross clamping, 5: the moment that the cuff pressure was at the lowest value during aortic cross-clamping, 6: after aortic declamping, 7: at the end of the CPB, 8: at the end of the operation. Results.- Cuff pressure was decreased when the body temperature was decreased. A strong positive correlation was obtained between esophageal temperature and cuff pressure (r= 0.79) and poor correlation was found between MAP and cuff pressure (r=0.49). Conclusion.- In this study during the hypothermic phase of CPB a significant decrease was occurred in cuff pressure. With the decrease in cuff pressure, the pressure exerted by the cuff on the tracheal wall is decreased. Therefore we conclude that during CPB, mucosal ischemia which can be occurred due to reduction in tracheal mucosal perfusion pressure can be prevented.